Comprehensive In Silico Characterization and Expression Profiling of TCP Gene Family in Rapeseed - Wen, Yunfei; Raza, Ali; Chu, Wen; Zou, Xiling; Cheng, Hongtao; Hu, Qiong; Liu, Jia; Wei, Wenliang (Frontiers in Genetics, 2021)
TCP proteins are plant-specific transcription factors that have multipurpose roles in plant developmental procedures and stress responses. Therefore, a genome-wide analysis was performed to categorize the TCP genes in the rapeseed genome. In this study, a total of 80 BnTCP genes were identified in the rapeseed genome and grouped into two main classes (PCF and CYC/TB1) according to phylogenetic analysis. The universal evolutionary analysis uncovered that BnTCP genes had experienced segmental duplications and positive selection pressure. Gene structure and conserved motif examination presented that Class I and Class II have diverse intron-exon patterns and motifs numbers. Overall, nine conserved motifs were identified and varied from two to seven in all TCP genes; and some of them were gene-specific. Mainly, Class II (PCF and CYC/TB1) possessed diverse structures compared to Class I. We identified four hormone- and four stress-related responsive cis-elements in the promoter regions. Moreover, 32 bna-miRNAs from 14 families were found to be targeting 21 BnTCPs genes. Gene ontology enrichment analysis presented that the BnTCP genes were primarily related to RNA/DNA binding, metabolic processes, transcriptional regulatory activities, etc. Transcriptome-based tissue-specific expression analysis showed that only a few genes (mainly BnTCP9, BnTCP22, BnTCP25, BnTCP48, BnTCP52, BnTCP60, BnTCP66, and BnTCP74) presented higher expression in root, stem, leaf, flower, seeds, and silique among all tested tissues. Likewise, qRT-PCR-based expression analysis exhibited that BnTCP36, BnTCP39, BnTCP53, BnTCP59, and BnTCP60 showed higher expression at certain time points under various hormones and abiotic stress conditions but not by drought and MeJA. Our results opened the new groundwork for future understanding of the intricate mechanisms of BnTCP in various developmental processes and abiotic stress signaling pathways in rapeseed.